Public Policies, Bioethics and Human Rights With Respect to Assisted Reproduction Serodiscordant’s Couples - Bageston, Vivian Nilson; Lima Both, Tatiana (Revista de Psicologia da IMED, 2013)
The success of antiretroviral therapy (HAART) for HIV has enabled excellent life expectancy for patients with HIV / AIDS and classified it as a treatable chronic disease, such reduction in morbidity and mortality. Thus, today, many carriers are in full reproductive age and, of course, are eager to have a family. This reading has mobilized an interview with a serodiscordant couple, and the data collected provided a proposal for dialogue between public policies, human rights and bioethics regarding assisted reproduction (AR) with serodiscordant couples. Entrenato not met, both in the area of human rights, and in bioethics and public policy, any clear position on the matter. Likewise, psychology is not observed in any of the areas discussed to assist in the reflection of the conflict between desire and decide to have a child.